Synthesis of bis(indolyl)methanes using ammonium niobium oxalate (ANO) as an efficient and recyclable catalyst1. Issue 8 (3rd August 2015) - Mendes, Samuel R.; Thurow, Samuel; Penteado, Filipe; da Silva, Maitê S.; Gariani, Rogério A.; Perin, Gelson; Lenardão, Eder J.
<x xml:space="preserve">Abstract</x> Bis(indolyl)methanes were efficiently synthesized using ammonium niobium oxalate (ANO) as the catalyst and water or glycerol as the solvent.